2022
DOI: 10.1111/jgh.15921
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota in eosinophilic esophagitis: A systematic review

Abstract: Author contribution: KAA meditated the project, reviewed papers and drafted the paper. EQA and GB contributed to the design of the study and review of papers identified at each stage. EH, JM, SK and AC provided manuscript concept, revised the drafts and critically edited the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
(94 reference statements)
1
10
0
Order By: Relevance
“…Patients with active EoE present changes in the esophageal microbiota and increased or decreased levels of particular species such as Haemophilus Fusobacterium, Aggregatibacter, and Actinomyces. However, studies show conflicting results for individual families, such as Streptococcaceae [ 52 ]. It may be worth focusing on Haemophilus because some studies demonstrated that their abundance was particularly high in EoE subjects, and it is associated with a range of other Th2-mediated conditions [ 52 ].…”
Section: Etiologymentioning
confidence: 99%
“…Patients with active EoE present changes in the esophageal microbiota and increased or decreased levels of particular species such as Haemophilus Fusobacterium, Aggregatibacter, and Actinomyces. However, studies show conflicting results for individual families, such as Streptococcaceae [ 52 ]. It may be worth focusing on Haemophilus because some studies demonstrated that their abundance was particularly high in EoE subjects, and it is associated with a range of other Th2-mediated conditions [ 52 ].…”
Section: Etiologymentioning
confidence: 99%
“…They make up to 90% of the cells in a ratio of 10:1. The microbiome’s composition is highly dynamic and dependent on host-associated factors such as age, diet, and environmental conditions [ 194 , 195 , 196 , 197 , 198 ] with the major phyla being Actinobacteria , Bacteroidetes , Firmicutes , and Proteobacteria . Diet, age, stress, antibiotics, xenobiotics, viruses, bacteria, parasites and diseases increase or decrease the relative abundance and diversity of bacterial species in the GI and other body sites.…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
“…Diet, age, stress, antibiotics, xenobiotics, viruses, bacteria, parasites and diseases increase or decrease the relative abundance and diversity of bacterial species in the GI and other body sites. Alterations in GI tract bacterial levels or diversity (dysbiosis) can disrupt mucosal immunological tolerance, leading to allergic diseases including food allergy (FA) [ 195 , 199 ] and asthma and other infectious disorders [ 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 ]. Allergic diseases include heterogeneous inflammatory pathologies, such as respiratory and food allergies (FA), which are characterized by an immunological response with Th2 lymphocytes producing IL-4, IL-5, and IL-13 and low production of IFN-γ [ 195 , 199 ] and (Th9) producing IL-9 and IL-10 [ 196 ] as the main effector T cells.…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
See 2 more Smart Citations